Catalyst design concept based on a variety of alloy materials: a personal account and relevant studies. Issue 31 (2nd July 2020) - Furukawa, Shinya; Komatsu, Takayuki; Shimizu, Ken-ichi
Abstract : An overview of a variety of advanced alloy materials for catalytic use is provided. Abstract : An overview of our recent advances in the development of highly efficient alloy materials for catalytic applications (intermetallic compounds, pseudo-binary, solid-solution, and single-atom alloys, and their derivatives) is provided as a personal account for the design of alloy-based catalysts. A series of important and emerging alloy materials and derivatives developed by other researchers for catalytic processes, such as Heusler alloys, high-entropy alloys, and rooted catalysts, are also introduced to cover a wide variety of such catalytic materials. The presented alloy materials are classified into (1) ordered, (2) disordered (random), and (3) precursors for nanocomposites, and each of them is further classified into subcategories based on their structure differences. The role of the metal elements, structural factors, and electronic properties in enhanced catalysis is also briefly explained by atomic scale interpretation.